Ecopreneurship Berbasis Digital Marketing untuk Meningkatkan Pendapatan Ibu PKK Desa Gunung Pasir Jaya - Theresia Dhian (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: Ecopreneurship provides solutions to the problems of waste with the aim of creating new value-added products. Ecopreneurs see the environment as something that must be preserved and maintained so that they can generate income. And to expand market reach in business, digital marketing is needed. Methodology: The method used is to develop awareness for PKK mothers regarding the value-added of waste with the target of 15 respondents in Gunung Pasir Jaya Village Lampung Timur. The presenters divided the training into two parts;Â  first, a training on the introduction of ecopreneurship through creative waste management to create selling points; second, a training on Digital Marketing using the Google My Business Application. Results: The result of the activity was that they made a mini sofa with eco-bricks. And they also introduce their business through Google My Business Application. Conclusion: The contribution of this activity, is that PKK mothers at Gunung Pasir Jaya can be more creative because they have awareness, knowledge, and experience from waste management in their environment to become interesting products that have economic value. And they have the knowledge to expand their business through digital marketing using Google My Business.